VD_FINDINFO HC / 2011 / 569 vom 23. September 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, CONJOINT, AVANCE DE FRAIS, VALEUR LITIGIEUSE | 159 al. 3 CC, 163 al. 1 CC, 163 al. 2 CC, 173 al. 3 CC, 176 al. 1 ch. 1 CC, 276 al. 1 CPC (CH), 308 al. 2 CPC (CH)